2010
DOI: 10.1371/journal.pone.0009062
|View full text |Cite
|
Sign up to set email alerts
|

DKK1 Mediated Inhibition of Wnt Signaling in Postnatal Mice Leads to Loss of TEC Progenitors and Thymic Degeneration

Abstract: BackgroundThymic epithelial cell (TEC) microenvironments are essential for the recruitment of T cell precursors from the bone marrow, as well as the subsequent expansion and selection of thymocytes resulting in a mature self-tolerant T cell repertoire. The molecular mechanisms, which control both the initial development and subsequent maintenance of these critical microenvironments, are poorly defined. Wnt signaling has been shown to be important to the development of several epithelial tissues and organs. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 92 publications
6
52
1
Order By: Relevance
“…Consistent with the latter hypothesis, decrease in the mTEC/cTEC ratio is observed in normal age-related thymic involution in wild-type mice and in pathologic thymic atrophy in several mutant mice. 13,14,31 In conclusion, we show here that Wnt4 regulates the expansion of both immature thymocytes and TECs with the net effect of increasing total cellularity in the fetal as well as early postnatal and adult thymus. Together with our previous report on the role of Wnt4 in thymic recovery post-HCT, 23 our data suggest that Wnt4, or its downstream effectors, would make very interesting candidates for countering thymic insufficiency and atrophy.…”
Section: Wnt4 In Fetal and Postnatal Thymopoiesis 5171supporting
confidence: 52%
See 2 more Smart Citations
“…Consistent with the latter hypothesis, decrease in the mTEC/cTEC ratio is observed in normal age-related thymic involution in wild-type mice and in pathologic thymic atrophy in several mutant mice. 13,14,31 In conclusion, we show here that Wnt4 regulates the expansion of both immature thymocytes and TECs with the net effect of increasing total cellularity in the fetal as well as early postnatal and adult thymus. Together with our previous report on the role of Wnt4 in thymic recovery post-HCT, 23 our data suggest that Wnt4, or its downstream effectors, would make very interesting candidates for countering thymic insufficiency and atrophy.…”
Section: Wnt4 In Fetal and Postnatal Thymopoiesis 5171supporting
confidence: 52%
“…9,10 Although thymic epithelial cells (TECs) provide growth factors and signals that will promote migration and T lineage commitment to the developing lymphocytes, the presence of lymphocytes is also necessary for the differentiation and functional maturation of TECs. 11,12 Postnatal disruption of TECs results in thymic atrophy, 13,14 whereas restoration of thymocyte development can reestablish TEC architecture in cases where the defect was thymocyte intrinsic. 15,16 Several studies have shown the importance of proper regulation of Wnt signaling during T-cell development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CD45 − EpCAM + TECs, MHC II lo , and MHC II hi subsets have been shown to represent the immature and mature TECs, respectively [31][32][33]. We found that rFOXN1 treatment increased the number of both MHC II lo immature and MHC II hi mature TECs 2 days and 1 month after HSCT (Supporting Information Fig.…”
Section: Rfoxn1 Increases the Number Of Total Tecs And Thymocytes In mentioning
confidence: 71%
“…These results suggest that FOXN1 induced mTEC proliferation is due, at least in part, to the enhanced expression of cyclin D1. Whether cyclin D1 and p53 are the directly or indirectly downstream target genes remains to be determined.In addition to an increased number of mature TECs, rFOXN1 treatment also increased the number of MHC II lo immature TECs.Several investigators have also shown that, in addition to maintain existing TECs, FOXN1 also regulates TEC progenitors [15,16,18,27,31], which may also contribute to the increased number of TECs. The number of ETPs was also significantly increased after rFOXN1 treatment.…”
mentioning
confidence: 99%